The Effect Of Traditional Game Approach On Improving Motivation And Learning Outcomes Of Physical Education - Farid Adnan Amrullah; Bambang Priyono; Harry Pramono (JUARA : Jurnal Olahraga, 2023)
Traditional games are part of the culture and traditions of a society and play an important role in maintaining and preserving cultural heritage. In traditional games, there are elements of basic motion both locomotor, non-locomotor and motion manipulation. The method in this study using quantitative methods with one group Pretest-Posttest Design study design without using the control group. Data collection techniques or instruments used by researchers in the form of assessment of Psychomotor, affective and cognitive aspects of the traditional game approach.The results of traditional game approach research can be an effective alternative in improving the learning outcomes of health care providers. Traditional game approach can help improve the effectiveness of the motivation of students in learning health care, so it needs to be considered in the design of learning strategies.The conclusion of the traditional game approach can be used as learning to students with high motivation. This research is expected to be used as input for PJOK teachers in an effort to optimize physical education learning